A STUDY ON CONSUMER ATTITUDE TOWARDS ONLINE SHOPPING IN KARNATAKA AND ITS OBSTACLES - VijayaKumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fashion of e-commerce has been elevated swiftly in recent years with the development of the Internet and due to the smooth accessibility of Internet utilization. Easy access to the Internet has driven clients to shop on-line. A maximum commercial enterprise corporation walking with the technological modifications, due to globalization they are focusing greater on meeting the wishes of the customers. We have also decided to have a look at the consumer's mind-set towards on line purchasing, especially the information approximately elements which played a function as obstacles in the course of on line shopping. The population of the examine is selected from the one of a taluk of tumkur district of Karnataka. The sample size is 60 and we've used a convenient sampling approach for the take a look at. Our findings suggest that in the demographic information career of the respondents not at all essential within the decision-making procedure, whereas it's also concluded that elderly human beings aren't in any respect interested in on line buying and for education, undergraduate and postgraduates are extra attracted toward online shopping. The research additionally suggests a few elements as boundaries to the consumers in the direction of on line shopping which include involved about giving credit card numbers, worry of wrong/horrific satisfactory product arrival, unawareness about easy returns and changing of objects, misleading fake reviews of products, featured merchandise aren't meeting expectations. It is anticipated that this observe will help on-line stores in karnataka to plan successful techniques for increasing e-commerce business and they are able to build better relations with customers.